The Status of Innovation Value Chain in One of Malaysia Public Research Institutes and Government Agencies - Ishak, Iskandar Shah; Alias, Rose Alinda; Abu, Hassan R; Basaruddin, S; Suradi, Z. (2013)
Innovation is an important aspect for organization to succeed in the competitive environment. Although innovation in organization can be seen through many perspectives, innovation value chain is helpful to view innovation. As sometimes organization could not find what are the reason and weaknesses that affect unsuccessful innovation implementation, innovation value chain assessment can help to identify these weaknesses. This paper presents the status of innovation value chain in one of Malaysia Public Research Institutes and Government Agencies and provides guidance to help solving an organization’s weaknesses. A survey questionnaire was sent to 170 staffs in an organization representing one of Malaysia Public Research Institutes and Government Agencies. The findings of the study show that the organization had innovation culture that cultivates innovation in their organization. However, the organization needs to improve in idea generation and idea conversion phases. The research recommends a guideline that could also benefit organization that have same problematic scenario.